2014
DOI: 10.1002/clen.201300264
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Dynamics During Flood Events in Tropical Catchments: A Case Study in Southern Vietnam

Abstract: Assessing surface water quality variation as well as chasing water pollution sources is essential for water quality management. However, for existing conditions in developing countries, this assessment may not be done properly in many affected catchments due to limited data and lacking of tools. In particular, pollutant transport from the catchment to its river system during flood events needs quantification and is the aim of the study. For this, a combined water quality monitoring and modeling approach is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This also suggested that TSS and Fe pollutions of La Buong river is rather a natural phenomenon which are intensi ed in wet season by surface run-off. This phenomenon was also observed in another study in Dong Nai river basin (Quan and Meon 2015). Therefore, a proper abatement scheme for TSS and Fe pollution should consider controlling of pollution sources by land-use practices in wet season combined with water treatment solutions before using.…”
Section: Temporal Patterns Of Variables and Drivers Of Pollutionsupporting
confidence: 63%
“…This also suggested that TSS and Fe pollutions of La Buong river is rather a natural phenomenon which are intensi ed in wet season by surface run-off. This phenomenon was also observed in another study in Dong Nai river basin (Quan and Meon 2015). Therefore, a proper abatement scheme for TSS and Fe pollution should consider controlling of pollution sources by land-use practices in wet season combined with water treatment solutions before using.…”
Section: Temporal Patterns Of Variables and Drivers Of Pollutionsupporting
confidence: 63%
“…The only identified point source of wastewater comes from a factory which produces tapioca starch from cassava (tapioca) roots. The company produces on average 30 tons of tapioca starch per day, which generates about 360-600 m 3 of wastewater per day [50]. An analysis of the water quality data of the main Tay Ninh river can be found in Nguyen and Meon [3].…”
Section: Study Areamentioning
confidence: 99%
“…Eutrophication can be seen as a consequence of excessive nutrients, which can lead to serious environmental problems such as limited water supply, severe hypoxia, and polluted aquatic ecosystems. Through the food chain, water pollution can cause serious waterborne diseases to human [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Though located in the tropical region with potential water resources, Vietnam has been suffering from a water shortage in both quantity and quality [5]. Water is mostly being polluted by untreated wastewater from point and diffuse sources [6,7]. The study area Binh Thuan is one of those central arid provinces of Vietnam with low rainfall intensities, of which the total volume is unevenly distributed across the landscape [8].…”
Section: Introductionmentioning
confidence: 99%